PENGARUH GREEN HUMAN RESOURCE MANAGEMENT (GHRM) TERHADAP LOYALITAS PELANGGAN DAN KINERJA KEUANGAN PERUSAHAAN: PERAN MEDIASI KEPUASAN DAN RETENSI PELANGGAN - Setyanto, Achmad; Faeni, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to explore the influence of GHRM on customer loyalty and company financial performance, considering the mediating role of customer satisfaction and retention. The urgency of this study lies in the fact that companies that implement GHRM can gain a significant competitive advantage. This study uses a qualitative approach with data collection techniques that include in-depth interviews, observation, and document analysis. Semi-structured interview techniques are used to obtain in-depth information regarding GHRM practices, customer satisfaction, and customer loyalty. This study shows that GHRM has a positive influence on customer loyalty and company financial performance through the mediation of customer satisfaction and retention. The implementation of good GHRM practices can increase employee satisfaction, which in turn has a positive impact on customer experience.